Histological assessment of the effect of 50mW red laser on retina at variable time intervals: animal model - Qamar Aqeel Shams,; Ameen Mohammad Alsudani,; Mustafa Salih Almusawi, (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the histopathological effect of 50milliWatt red laser pointer on mice retinal tissue at variable exposure times. Method: The experimental study was conducted in the Postgraduate Laboratory of the Unit of Medical Physics, Department of Physiology, College of Medicine, Mustansiriyah University, Baghdad, Iraq, from November 2020 to April 2021, and comprised albino mice. Histopathological effects on the retinal tissues were evaluated microscopically using conventional haematoxylin and eosin stain just after being exposed to commercially available 50 milliWatt red laser pointers with 630nm wavelength at 1, 2 and 3 minutes, grouped as R1, R2 and R3, respectively. The laser beam was focussed on the right eye of the mice sedated with sodium pentobarbital, reserving the left eye for use as a control group. Data was analysed using SPSS 24. Results: Of the 12 mice, 4(33.3%) were in each of the 3 groups. There was significantly destructive effect of red laser on retinal outer cellular layers in all the groups compared to the controls (p<0.05). The effect was significant between R1 and R2 (p=0.0001), and between R2 and R3 (p=0.02). Conclusion: The handheld commercial red laser pointers could harmfully affect a wide range of mice retina and choroid. Key Words: Eosine, Pentobarbital, Retina, Lasers, Choroid, Sodium